2018 Atmospheric Flight Mechanics Conference 2018
DOI: 10.2514/6.2018-3560
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurements of Fuel Savings During Aircraft Wake Surfing

Abstract: completed a series of research flights to better understand the challenges of aircraft wake surfing using civilian airplanes and commercial avionics. The research flights sought to demonstrate significant fuel savings by a pair of business jets engaged in automated wake surfing using commercial off-the-shelf avionics to the fullest extent possible, including a 1090-MHz Automatic Dependent Surveillance -Broadcast (ADS-B) data link. A NASA Gulfstream C-20A airplane (Gulfstream Aerospace, Savannah, Georgia) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A significant flight test conducted in 2013 focused on maneuvers, procedures, human factors, safety, and compatibility with normal operations and air traffic control. NASA continued flight testing, most recently in the Gulfstream III, validating the use of Automatic Dependent Surveillance-Broadcast (ADS-B) as a datalink 10 . Commercial companies such as Lockheed-Martin and Airbus, academia, and government research laboratories (e.g., the Deutsches Zentrum für Luft-und Raumfahrt, DLR) have conducted extensive modeling and simulation and flights for AWSE.…”
Section: A Historymentioning
confidence: 99%
“…A significant flight test conducted in 2013 focused on maneuvers, procedures, human factors, safety, and compatibility with normal operations and air traffic control. NASA continued flight testing, most recently in the Gulfstream III, validating the use of Automatic Dependent Surveillance-Broadcast (ADS-B) as a datalink 10 . Commercial companies such as Lockheed-Martin and Airbus, academia, and government research laboratories (e.g., the Deutsches Zentrum für Luft-und Raumfahrt, DLR) have conducted extensive modeling and simulation and flights for AWSE.…”
Section: A Historymentioning
confidence: 99%
“…[14]) for a detailed description of the pilot displays used for this flight experiment and Hanson (Ref. [15]) for more details regarding the wake surfing performance measurements and analysis.…”
Section: Flight Experiments Descriptionmentioning
confidence: 99%
“…The National Aeronautics and Space Administration (NASA) Armstrong Flight Research Center (Edwards, CA, USA) completed a series of studies, in which a NASA Gulfstream C-20A airplane (Gulfstream Aerospace, Savannah, GA, USA) was flown as the trail airplane within the wake of a NASA Gulfstream III (G-III) airplane. The results showed fuel reductions in formation ranging from 3.5 to 8 percent, compared with that of a single aircraft [18]. The optimal positioning of a flying wing aircraft behind a refueling plane was extensively investigated by Okolo et al [19], who revealed that any deviation from the static sweet spot, whether in the vertical or lateral direction, results in reductions in the lift-to-drag ratio benefit.…”
Section: Introductionmentioning
confidence: 99%